The Effectiveness of the Buerger Allen Exercise Intervention on Changes in Ankle Brachial Index Values in Diabetes Mellitus Patients: Literature Study - Fatima Ura Pabanne (NHM PRESS, 2023)
Research is a literature study. In the strategy of looking for journals, the framework used is PICOT. The keywords used were